Klaus Michael Meyer-Abich on Ecological Revolution - Paulina Selmaj-Pomaska (The Francis de Sales Scientific Society (TNFS.PL), 2022)
This article refers to K. M. Meyer-Abich's concept of ecological revolution mainly presented in his book "Revolution for Nature", where the author explained the idea of a holistic alternative to the Western world-view which remains under the questionable influence of the Enlightenment. The solution and termination of the so-called ecological crisis can only be achieved if people recognize their responsibilities towards all things in nature. Practical philosophy of nature determines such perspectives of human development, which are based on the principles founding and stabilizing the ethos of its ecological survival. K. M. Meyer-Abich talks about the principle of peace. This idea includes establishing peace with man, which is the first step towards establishing peace with nature.